1991
DOI: 10.1073/pnas.88.7.2628
|View full text |Cite
|
Sign up to set email alerts
|

A six-amino acid deletion in basic fibroblast growth factor dissociates its mitogenic activity from its plasminogen activator-inducing capacity.

Abstract: A recombinant deletion mutant of the 155-amino acid form of human basic fibroblast growth factor (bFGF), lacking amino acid residues 27-32 (Lys-Asp-Pro-Lys-Arg-Leu), was expressed in Escherichia coli and purified to homogeneity by heparin-Sepharose affinity chromatography. When maintained in the presence of an equimolar concentration of soluble heparin, the bFGF mutant (M1-bFGF) is as potent as bFGF in stimulating cell proliferation in normal and transformed fetal bovine aortic endothelial cells, in adult bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…In agreement with this hypothesis, we demonstrated that the mitogenic activity and urokinase-type plasminogen activator (uPA)-inducing capacity of FGF-2 are mediated by different signal transduction pathways in cultured endothelial GM 7373 cells (Presta et al, 1989). However, we observed also that different FGF-2 mutants devoid of the capacity to up-regulate uPA production in endothelial cells still retain receptor-binding activity and full mitogenic capacity (Isacchi et al, 1991;Presta et al, 1992Presta et al, , 1993, raising the question of the role exerted by TK-FGFR in transducing the uPA-inducing signal. This was examined also in light of the complexity of the mechanism of interaction of FGF-2 with the endothelial cell.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…In agreement with this hypothesis, we demonstrated that the mitogenic activity and urokinase-type plasminogen activator (uPA)-inducing capacity of FGF-2 are mediated by different signal transduction pathways in cultured endothelial GM 7373 cells (Presta et al, 1989). However, we observed also that different FGF-2 mutants devoid of the capacity to up-regulate uPA production in endothelial cells still retain receptor-binding activity and full mitogenic capacity (Isacchi et al, 1991;Presta et al, 1992Presta et al, , 1993, raising the question of the role exerted by TK-FGFR in transducing the uPA-inducing signal. This was examined also in light of the complexity of the mechanism of interaction of FGF-2 with the endothelial cell.…”
Section: Introductionsupporting
confidence: 72%
“…However, this interaction differs from that responsible for mitogenicity, as suggested by the biological properties of different FGF-2 mutants (Isacchi et al, 1991;Presta et al, 1992Presta et al, , 1993 and confirmed by the experiments performed here with various FGF-2 antagonists.…”
Section: Fgf-2 Antagonists and Upa Up-regulationmentioning
confidence: 66%
See 3 more Smart Citations